PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN IBU DALAM PENANGANAN AWAL KEJANG DEMAM PADA BALITA - Marwan Riki Ginanjar; Hallya Ellyanti; Sri Tirtayanti (Masker Medika, 2024)
Background: Toddlers are children under 5 years old so that children aged 1 to 5 years are included in this group. Most toddlers have a greater risk of developing a disease, namely febrile seizures. Febrile seizures are seizures that occur in children who have a fever without a central nervous system infection that occurs more than 38°C. Knowledge of early treatment of febrile seizures is very necessary to treat febrile seizures in toddlers, one of which is through health education. The selection of the chalk and talk method can help mothers increase their knowledge about early treatment of febrile seizures in toddlers. Objective: To determine the effect of health education using the chalk and talk method on mothers' knowledge in early treatment of febrile seizures in toddlers. Method: This type of quantitative research with Pre-Experimental One Group Pre-Test and post-Test Design, this study was conducted in August 2024 with a sample of 32 respondents in the Mawar Putih Mariana Health Center work area. The provision of knowledge using the chalk and talk method, the results of the knowledge were measured using a questionnaire. The results of the analysis used the paired samples t-test. Results: The average value of knowledge before health education was 9.22 and after health education was 12.81 with a p-value <0.05. Conclusion: There is an effect of chalk and talk method health education on mothers' knowledge in early handling of febrile seizures in toddlers.